Pengembangan E-Modul Berbasis Android pada Mata Kuliah Seni Lukis Dasar - Ferdian Ondira Asa; San Ahdi; Defrizal Saputra (Jurnal Pendidikan dan Pengajaran, 2026)
The problem addressed in this study is the suboptimal use of technology-based teaching materials in basic painting courses, resulting in learning processes that still tend to be conventional and less flexible. This condition has an impact on students’ low learning independence and the less-than-optimal improvement of learning outcomes. The main objective of this study is to develop an Android-based e-module to improve students’ learning outcomes in the basic painting course. This study employed a development research method using the ADDIE model, which consists of several stages: analysis, design, development, implementation, and evaluation. The research subjects were 30 odd-semester university students. The instruments used were questionnaires in the form of validation sheets completed by experts and students. Data were collected through interviews, documentation, and questionnaire distribution. The obtained data were analyzed using the ADDIE model and tested for validity, practicality, and effectiveness. The results showed that the Android-based e-module was feasible and effective for use. In general, the findings indicate that the development of the Android-based e-module is feasible, practical, and effective as teaching material for the basic painting course, and it is capable of addressing the problem of the low optimization of technology in learning and improving students’ learning outcomes. The implications of this study suggest that Android-based e-modules can serve as an alternative digital teaching material that supports independent, flexible, and interactive learning in higher education, while also encouraging the systematic integration of technology in the development of art learning media.